A Research-Informed Approach to Curriculum Development: Designing a Vocational English Course for a Specific Topic in Graphic Design - Syairofi, Ahmad; Suwarno, Suwarno (SALEE: Study of Applied Linguistics and English Education, 2025)
Since the inception of vocational secondary schools in Indonesia, the English curriculum for such schools has been considered general English rather than vocational English, which serves as the medium of English learning for the students’ future work. This issue becomes a challenge for English teachers to design their courses to align with what has been mandated in the national curriculum and, simultaneously, the students’ needs according to their major of study. To address this issue, this paper examines vocational English curriculum designs from the literature. It uses their insights to develop an English curriculum design for specific topics in a vocational secondary school context. Vocational English curriculum designs from two countries (i.e., Taiwan and Poland) and five ESP course development models from prominent academic studies were analyzed. The analysis concerns the four key aspects of ESP (i.e., needs analysis, learning objectives, materials and methods, and evaluation). This paper makes explicit the curriculum development processes in ESP courses and proposes a course design model for a specific topic in graphic design.